Prevalence of Type 2 Diabetes Mellitus in Rural Adults (>_31years) in Bangladesh (Faridpur Medical College Journal, 2018)
Diabetes is one of the most prevalent and serious non- communicable diseases all over the world. It is the leading cause of death, disability, and economic loss, and it is identified as a major threat to global development. Among the adults (age 20-79 years) with diabetes in the top five South East Asian countries, Bangladesh is in the second position. The number of people with diabetes in Bangladesh was 5.10 million in 2013, which is expected to increase to 8.20 million by 2035. Therefore, this study aimed to estimate the prevalence of type 2 diabetes in a rural population aged >_ 31 years living at a village in the district of Bagerhat, Bangladesh, and to aware the people of the area about diabetes and to detect diabetes early for early care to prevent its complications. In this study we used 'Prodigy Preferred blood Glucose Meter' for testing fasting blood glucose to diagnose diabetes. The study was conducted from 2012 to 2015. Random sampling method was used to select participants. Fasting plasma glucose of the 400 participants of >_ 31 years of age was done at a 'Free Friday Clinic' of the study area. Out of 400 participants 38 (09.50%) were diabetic. Among the participants (n=400), 45.50% were male and 54.50% were female. We found a high prevalence of DM in the rural Bangladeshi adult population (9.5%). The present study found that about one in ten Bangladeshi adults has diabetes (9.5%). This finding is consistent with many other studies from low-and middleincome countries including India (8.6%), Sri Lanka (8.0%), China (9.6%), Nauru (13.7%), and Panama (9.5%). Our study together with previous study confirms that prevalence of diabetes is increasing in Bangladesh.Faridpur Med. Coll. J. Jan 2018;13(1): 20-23